Incretin hormones as immunomodulators of atherosclerosis - Alonso, Nuria; Julián, María Teresa; Vives-Pi, Marta; Puig-Domingo, Manuel (Frontiers in Endocrinology, 2012)
Atherosclerosis results from endothelial cell dysfunction and inflammatory processes affecting both macro-and microvasculature which are involved in vascular diabetic complications. Glucagon-like peptide 1 (GLP-1) is an incretin hormone responsible for amplification of insulin secretion when nutrients are given orally as opposed to intravenously and it retains its insulinotropic activity in patients with type 2 diabetes mellitus (T2D). GLP-1 based therapies, such as GLP-1 receptor (R) agonists and inhibitors of dipeptidyl peptidase 4 (DPP-4), an enzyme that degrades endogenous GLP-1 are routinely used to treat patients with T2D. Recent experimental model studies have established that GLP-1R mRNA is widely expressed in several immune cells. Moreover, its activation contributes to the regulation of both thymocyte and peripheral T cells proliferation and is involved in the maintenance of peripheral regulatory T cells. GLP-1 R is also expressed in endothelial and smooth muscle cells. The effect of incretin hormones on atherosclerogenesis have recently been studied in animal models of apolipoprotein E-deficient mice (apo E-/-). These studies have demonstrated that treatment with incretin hormones or related compounds suppresses the progression of atherosclerosis and macrophage infiltration in the arterial wall as well as a marked anti-oxidative and anti-inflammatory effect on endothelial cells. This effect may have a major impact on the attenuation of atherosclerosis and may help in the design of new therapies for cardiovascular disease in patients with type 2 diabetes.